(untitled) - Northington, David K. (Dubuque, IA, 1996)
This lab manual provides a broad survey of botanical materials, emphasizes some of the more important relevant biological concepts, includes sufficiently clear and detailed instructions to make possible independent work by each student and allows an experimental approach wherever possible.
Keywords: Botany,Thực vật học